Equilibrium States of Galactic Atmospheres. II. Interpretation and Implications - G. Mark Voit; Christopher Carr; Drummond B. Fielding; Viraj Pandya; Greg L. Bryan; Megan Donahue; Benjamin D. Oppenheimer; Rachel S. Somerville (The Astrophysical Journal)
The scaling of galaxy properties with halo mass suggests that feedback loops regulate star formation, but there is no consensus yet about how those feedback loops work. To help clarify discussions of galaxy-scale feedback, Paper I presented a very simple model for supernova feedback that it called the minimalist regulator model. This follow-up paper interprets that model and discusses its implications. The model itself is an accounting system that tracks all of the mass and energy associated with a halo’s circumgalactic baryons—the central galaxy’s atmosphere. Algebraic solutions for the equilibrium states of that model reveal that star formation in low-mass halos self-regulates primarily by expanding the atmospheres of those halos, ultimately resulting in stellar masses that are insensitive to the mass-loading properties of galactic winds. What matters most is the proportion of supernova energy that couples with circumgalactic gas. However, supernova feedback alone fails to expand galactic atmospheres in higher-mass halos. According to the minimalist regulator model, an atmospheric contraction crisis ensues, which may be what triggers strong black hole feedback. The model also predicts that circumgalactic medium properties emerging from cosmological simulations should depend largely on the specific energy of the outflows they produce, and we interpret the qualitative properties of several numerical simulations in light of that prediction.